KERAHASIAAN BANK SUATU TINJAUAN DALAM ATURAN HUKUM PERBANKAN SYARIAH DI INDOESIA - Miftah Idris (Al-Amwal : Journal of Islamic Economic Law, 2016)
Islamic Banking is part of the financial and payment system of a country and its existence depends absolutely on the confidence of the customers who entrust their deposits in the Islamic Banking, so the bank secrecy is necessary to maintain it. Bank secrecy as defined under the Act is everything related to the financial and other matters of bank customers in the ordinary course of banking world shall be kept confidential in this case Islamic banking. In this paper there would discuss how was the actual secrecy Islamic bank in Indonesia in accordance with the applicable law and how it was applied in the field. This was written to determine the scope of bank secrecy in Islamic banking and exceptions set out in secrecy banks in Islamic banking in Indonesia.